Antibacterial Activity of Citrus sinensis (Orange) Peel on Bacterial Isolates from Wound - Abalaka, M. E; Bello, A. O. (UMYU Journal of Microbiology Research)
The antibacterial activity of aqueous, ethanolic and ethyl acetate extracts of Citrus sinensis against Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa was determined. This work aimed to discover the effects of orange peels extracts in the treatment of wounds contaminated by bacteria. Four different concentrations (50mg/ml, 100mg/ml, 150mg/ml, and 200mg/ml) of each extract were used against the test organisms. The test isolates demonstrated susceptibility to the varying concentrations of the crude extracts; this was evident in the different diameters of zones of inhibition displayed by the extracts. Staphylococcus aureus was the least susceptible to the various extracts at different concentrations. The aqueous extract showed a zone of inhibition of 7±0.0mm at 50mg/ml and 16±2.0mm at 200mg/ml against Escherichia coli; Pseudomonas aeroginosa at 7±0.0mm, 50mg/ml and 15±1.0mm at 200mg/ml; Klebsiella pneumoniae 6±0.0mm at 50mg/ml and 15±1.0mm at 200mg/ml. Ethyl acetate produce the zone of inhibition of 9±0.0mm and 19±1.0mm with Klebsiella pneumoniae at 50mg/ml and 200mg/ml; Escherichia coli at 8±0.0mm and 14±1.0mm at 50mg/ml and 200mg/ml respectively; Pseudomonas aeroginosa was susceptible to ethanol extract giving zones of inhibition of 6±0.0mm and 14±0.0mm at the concentrations of 50mg/ml and 200mg/ml respectively. The result showed that the potency and efficacy of the orange peel extracts on the organisms that cause wound infection had different hierarchy of susceptibility among the test organisms. The crude extracts from orange peels may be used to disinfect wounds and probably lead to cure if it can be properly refined.